Transition into Liminal Legality: DACA's Mixed Impacts on Education and Employment among Young Adult Immigrants in California. (1st May 2020) - Hamilton, Erin R; Patler, Caitlin; Savinar, Robin
Abstract: The Deferred Action for Childhood Arrivals (DACA) program, implemented by executive order in 2012, granted a subset of undocumented youth temporary relief from deportation, work authorization, and other benefits. While theories of immigrant integration predict that legalization will enable immigrant socioeconomic mobility, past research on DACA's effects on education and employment have reached mixed conclusions, possibly reflecting the limitations of different methodological approaches to the question. Using multiple data sources and mixed methods, we analyzed both whether and how DACA impacted education and employment among undocumented immigrants in California. Our difference-in-differences analysis of the 2007–2017 waves of the California Health Interview Study employs a more precise definition of the DACA-eligible population than previous studies, yet we also find mixed effects. Our analysis of surveys and in-depth interviews collected with DACA recipients in California provides context for this finding. DACA enabled college for some, but discouraged it for others. DACA recipients perceived substantial occupational mobility, but this was not reflected in movement out of the secondary labor market for many. Our findings suggest that without access to permanent legal status, DACA recipients will experience liminal legality with limited and contingent impacts on socioeconomic integration.